2021
DOI: 10.1186/s12876-021-01635-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum ATX and LPA as potential diagnostic biomarkers in patients with pancreatic cancer

Abstract: Background Pancreatic cancer (PC) is a devastating disease that has a poor prognosis and a total 5-year survival rate of around 5%. The poor prognosis of PC is due in part to a lack of suitable biomarkers that can allow early diagnosis. The lysophospholipase autotaxin (ATX) and its product lysophosphatidic acid (LPA) play an essential role in disease progression in PC patients and are associated with increased morbidity in several types of cancer. In this study, we evaluated both the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
(12 reference statements)
2
12
0
Order By: Relevance
“…Moreover, alterations in LPA can also result in neurodevelopmental disturbances and neuropsychiatric diseases, such as schizophrenia, Alzheimer's disease, and autism [15,16]. As the ATX-LPA axis is usually altered under these pathological states, circulating concentrations of ATX and/or LPA species have been proposed as new biomarkers for the detection of relevant diseases, such as different types of cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alterations in LPA can also result in neurodevelopmental disturbances and neuropsychiatric diseases, such as schizophrenia, Alzheimer's disease, and autism [15,16]. As the ATX-LPA axis is usually altered under these pathological states, circulating concentrations of ATX and/or LPA species have been proposed as new biomarkers for the detection of relevant diseases, such as different types of cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PON3 had a low expression in hepatocellular carcinoma and ovarian serous papillary carcinomas (29,30). Besides, it was reported that LPA acted a pivotal part in the progression of pancreatic cancer and had relationship with certain types of cancer (31). Through the above data, interactions between PON1 and these genes revealed that PON1 might have a potential impact on the progression of KIRC.…”
Section: Discussionmentioning
confidence: 92%
“…A combination of ATX, LPA, and Ca19-9 improved diagnostic accuracy for early-stage PDAC compared to a control group with an AUROC of 0.983 ± 0.016 (p = 0.0012). A panel of ATX, LPA, and Ca19-9 enhanced the AUROC to 0.973 ± 0.023 (p = 0.0090) compared to the BPD group [29]. The levels of all three biomarkers could be used to detect early-stage PDAC patients from patients with BPD or from healthy populations.…”
Section: Lysophosphatidic Acid (Lpa) and Autotaxin (Atx)mentioning
confidence: 86%